2018
DOI: 10.1002/eat.22965
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to seeking treatment for eating disorders: The role of self‐recognition in understanding gender disparities in who seeks help

Abstract: Objective Previous research suggests that men with eating disorders are less likely to seek treatment than are women. Given stereotypes linked to eating disorders, men may be less likely to recognize when they have an eating disorder, which could act as a barrier to treatment‐seeking. Method The current study examined differences in self‐recognition and treatment‐seeking behavior by gender, controlling for other covariates, in participants with probable DSM‐5 eating disorders drawn from a larger community‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
3
38
6
1
Order By: Relevance
“…Although research has indicated that lack of recognition of symptoms presents a barrier to treatment (Ali et al, ; Grillot & Keel, ), in the present study, few relationships were observed between treatment‐seeking and reported levels of eating disorder symptoms. Higher treatment‐seeking intentions were associated with greater frequency of binge eating and recognition of greater negative impact of eating disorder symptoms on relationships and on well‐being, the latter findings on symptom impact providing support for past research (Regan et al, ).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Although research has indicated that lack of recognition of symptoms presents a barrier to treatment (Ali et al, ; Grillot & Keel, ), in the present study, few relationships were observed between treatment‐seeking and reported levels of eating disorder symptoms. Higher treatment‐seeking intentions were associated with greater frequency of binge eating and recognition of greater negative impact of eating disorder symptoms on relationships and on well‐being, the latter findings on symptom impact providing support for past research (Regan et al, ).…”
Section: Discussioncontrasting
confidence: 72%
“…Although research has indicated that lack of recognition of symptoms presents a barrier to treatment (Ali et al, 2017;Grillot & Keel, 2018), in the present study, few relationships were observed between treatment-seeking and reported levels of eating disorder symptoms.…”
Section: Discussioncontrasting
confidence: 71%
“…Given research indicating that eating disorders do not discriminate and that they affect individuals of all genders, ages, races, and ethnicities (Schaumberg et al, ), it is likely that the demographic characteristics of the current sample are a reflection of the sampling strategy utilized rather than a true reflection of the demographic characteristics of individuals with eating disorders in the U.S. Instead, it may be that stereotypes about eating disorders impact disorder recognition and who chooses to take the screen (e.g., Grillot & Keel, ; Räisänen & Hunt, ). In the future, screening initiatives, such as those reported in the current study, might be paired with campaigns dedicated toward improving awareness of the occurrence and adverse impact of eating disorder behaviors among individuals from marginalized demographic sectors (e.g., Mitchison, Hay, Slewa‐Younan, & Mond, ) to encourage greater participation in screening by such individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Research indicates that EDs do not discriminate and that they affect individuals of all genders, races, and ethnicities (Schaumberg et al, ). When screening methods rely on students self‐selecting to take the screen, as was done here, it may be that stereotypes about EDs influence who chooses to take the screen (e.g., Grillot & Keel, ; Räisänen & Hunt, ). In the future, screening initiatives might be paired with campaigns dedicated to improving awareness of the occurrence of EDs among individuals from minority groups (e.g., Mitchison, Hay, Slewa‐Younan, & Mond, ).…”
Section: Discussionmentioning
confidence: 99%